Rancang Bangun Website Kampung Batu Lubang Pantai sebagai Destinasi Wisata dan Sarana Promosi Pariwisata - Lina, Tirsa Ninia; Pormes, Frenny Silvia (Jurnal Teknologi Terpadu, 2024)
Kampung Batu Lubang Pantai is located in Makbon District, Sorong Regency, and is part of the marine tourism area in Southwest Papua. So far, tourists/visitors are primarily familiar with Tanjung Batu Lubang tourism, even though there are many other tourism potentials, such as beach tourism (Bainggik Beach, Bainggik Tengah, Klaswonik, Pasir Pendek, Kladimala, Tanjung Batu Lubang, Pasir Timbul), cultural attractions (A’len dance, Srar dance, Suling Tambur, traditional Moi Tribe houses), religious sites (Gospel Monument, Hill of the Cross), and local wisdom products (noken Banto, kal’uk head covers, kal’dala, kal’lagi, noken kwok ou ukisik, mats). This lack of awareness is due to the insufficient and incomplete dissemination of information, as well as the community’s limited understanding of IT utilization. The purpose of this research is to design and build a website for Kampung Batu Lubang Pantai to assist in spreading information related to village activities and tourist destinations, serving as a tourism promotion tool that can ultimately improve the welfare and economy of the community. The system development method uses the Waterfall model, which includes requirements, design, implementation, verification, and maintenance stages. The applications used include Balsamiq Mockups, draw.io, and Bracket Editor. The result of the research is a village website consisting of menus such as Beranda, Profil, Pemerintahan, Informasi, Galeri, Potensi, and Kontak. System testing using Black Box Testing showed that the menu functions were working well so that it could be handed over to the village.